Impaired pulmonary function in patients with psoriasis - يوسف, زينب; محمد الخير ,; محمد اسماعيل, (Latakia University Journal -Medical Sciences Series, 2022)
Abstract Background: The inflammation that occurs with psoriasis can affect lungs, and hence, pulmonary function should be studied in patients with psoriasis. Aim: The aim of this study was to compare the spirometric parameters in patients with psoriasis and controls. Materials and Methods: This case-control study was conducted at Tishreen University Hospital during the period from March 2020 to March 2021. Ninety-five patients with psoriasis and 80 sex- and age matched control subjects were included. Spirometric pulmonary function testing, including forced vital capacity (FVC), forced expiratory volume in the 1st second (FEV1), forced expiratory flow at 25–75% of FVC (FEF25–75%), and FEV1/FVC ratio, was performed in all study subjects. Results: The mean FEV1, FEV1/FVC ratio, and FEF25–75% were significantly lower in the psoriasis patients than in the controls. The prevalence of obstructive disorder was significantly higher in patients with psoriasis (17.9% vs. 7.5%, P<0.05). The prevalence of obstructive disorder in patients with psoriasis was independent of the patient's sex and obesity. Smoking has increased the risk of obstructive disorder compared to controls (odds ratio 3.37). The presence of a severe psoriasis (PASI > 12) has increased the risk of pulmonary obstructive disorder (odds ratio 3.22). Conclusion: In this study, psoriasis was found to be associated with obstructive disorder. Dermatologists caring for patients with psoriasis should be aware of this association, consult a pulmonologist, and advise the patients to stop smoking and reduce additional risk factors for COPD.